2019
DOI: 10.1016/j.humimm.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The genetics, structure and function of the M1 aminopeptidase oxytocinase subfamily and their therapeutic potential in immune-mediated disease

Abstract: The oxytocinase subfamily of M1 aminopeptidases plays an important role in processing and trimming of peptides for presentation on major histocompatibility (MHC) Class I molecules. Several large-scale genomic studies have identified association of members of this family of enzymes, most notably ERAP1 and ERAP2, with immune-mediated diseases including ankylosing spondylitis, psoriasis and birdshot chorioretinopathy. Much is now known about the genetics of these enzymes and how genetic variants alter their funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 113 publications
1
21
0
Order By: Relevance
“…38) Overall, we postulated that ERAP1 is primarily secreted into the extracellular milieu; however, can be retained in the ER-lumen in the presence of putative binding proteins. 6,11) Further, we depleted the exon 10 coding sequence, and observed that the mutant enzyme was no longer retained in the ER-lumen and was constitutively secreted into the culture medium; thereby, supporting our hypothesis. 13) It is plausible that saturation with putative binding protein resulted in free residual ERAP1 in the ER-lumen, which was then secreted into the extracellular milieu.…”
Section: Secretion Of Erap1supporting
confidence: 77%
See 1 more Smart Citation
“…38) Overall, we postulated that ERAP1 is primarily secreted into the extracellular milieu; however, can be retained in the ER-lumen in the presence of putative binding proteins. 6,11) Further, we depleted the exon 10 coding sequence, and observed that the mutant enzyme was no longer retained in the ER-lumen and was constitutively secreted into the culture medium; thereby, supporting our hypothesis. 13) It is plausible that saturation with putative binding protein resulted in free residual ERAP1 in the ER-lumen, which was then secreted into the extracellular milieu.…”
Section: Secretion Of Erap1supporting
confidence: 77%
“…4) It is now well recognized that ERAP1 is primarily an antigenic peptide-processing enzyme located in the lumen of endoplasmic reticulum (ER-lumen), and involved in several autoimmune and inflammatory diseases. [5][6][7][8] However, there are additional activities of ERAP1 that have not been well documented to date. Here, we summarize multiple functions of ERAP1 enzyme outside ER-lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Given that ERAP1 and ERAP2 have similar contribution to the field and a high sequence homology (22) that allows them to function both as homodimers and heterodimers (2, 23), we decided to clarify the following questions regarding ERAP2: (1) can ERAP2 be secreted by immune-competent activated cells? (2) If this is the case, does secreted ERAP2 retain its anti-HIV-1 properties?…”
Section: Introductionmentioning
confidence: 99%
“…Beside the proteasome, ~20 proteases act in the MHC-I presentation pathway and can alter presented peptides (Lázaro et al, 2015). ERAP1 is probably the most relevant example here since this aminopeptidase plays a major role in antigen processing through N-terminal peptide trimming into the endoplasmic reticulum and is associated with a number of different autoimmune diseases (Hanson et al, 2018;Serwold et al, 2002). Other aminopeptidases such as methionine aminopeptidase 2 (METAP2), leucine aminopeptidase 3 (LAP3), peptidase D (PEPD) and dipeptidyl peptidase 4 (DPP4) were showcased in this study, the latter also known to be involved in TCR-MHC signaling (Ghersi et al, 2006;Wagner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%